Rainwater harvesting and ablution water recycling approaches for general usage in Universiti Teknologi Mara Pulau Pinang, Bertam Campus / Ir. Nur Azwa Muhamad Bashar - Muhamad Bashar, Nur Azwa (Unit Penerbitan FKAPP, 2020)
Malaysia is experiencing a tropical weather and receives rainfall throughout the year. In addition, Malaysia also experienced flooding and droughts season thus require a controllable measure to overcome the raised problems. Water shortage or water stress issue has been highlighted by most of the Countries andfurther effort should be taken into consideration to control the situation. Rainwater harvesting technique is said to be one of the solutions to this issue. In Malaysia, Rainwater Harvesting System (RHS) has been managed and controlled by the Department of Irrigation and Drainage (DID) Malaysia. The details guidelines for Rainwater Harvesting System (RHS) can be referred in the Manual Saliran Mesra Alam Malaysia (MASMA 2012).